Malaysia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper analyzes saving to understand history and identify the drivers in Malaysia. IMF analysis suggests that Malaysia's current account (CA) surplus is higher than warranted by medium-term fundamentals and desired policies. The changes in the corporate saving rate almost entirely reflect the changes within each group of firms of similar size or age. Leveraging firm-level data for listed firms, the paper focuses on the contribution to the CA surplus of private non-financial corporations. The trend analysis indicates a high dependence of listed firms in Malaysia on internal funds (savings) to finance their investments or, equivalently, a lower dependence on external funds. The results suggest that relaxing firms' external financing constraints and lifting productivity growth could help encourage investment and reduce excess corporate saving. The regression results show that the transaction cost and precautionary saving motives, as well as their interaction with external financing dependence, could play an important role in explaining corporate net saving.